Tocilizumab-Based Treatment of Microvascular Inflammation in Kidney Transplant Recipients: A Retrospective Study - Johan Noble; Johan Noble; Johan Noble; Giorgia Comai; Giorgia Comai; Valeria Corredetti; Reda Laamech; Celine Dard; Thomas Jouve; Thomas Jouve; Diane Giovannini; Audrey Le Gouellec; et al. (Transplant International)
Chronic-active antibody mediated rejection (caAMR) is the leading causes of long-term kidney graft failure. Tocilizumab (TCZ), an anti-IL-6 receptor antibody, has been suggested as a treatment, but data are conflicting. We retrospectively studied consecutive adult kidney transplant recipients with caAMR or microvascular inflammation (MVI) without Donor-Specific Antibodies (DSA) and without C4d deposition (MVI + DSA-C4d-), who received TCZ as first-line therapy in two European centers. Estimated glomerular filtration rate (eGFR) and DSA were assessed one-year before and after TCZ initiation. The study included 64 patients who received TCZ between July 2018 and September 2023. The eGFR trajectory significantly decreased after TCZ treatment (−1.2 ± 0.2 vs. 0.03 ± 0.2 mL/min/1.73 m2/month pre- vs. post-TCZ, respectively; p = 0.001). The percentage of patients with DSA decreased from 63.9% to 38.9% (p < 0.001), and the average MFI decreased from 9,537 to 7,250 (p = 0.001). In multivariate analysis, younger age (OR = 0.95, p = 0.02), MVI + DSA-C4d- phenotype (OR = 5.2, p = 0.01), and lower chronic glomerulopathy score (OR = 4.5, p = 0.02) were associated with TCZ response (trajectory ≥0 after TCZ). Patient survival was 98.4%, and graft survival was 93.7% at one-year. First-line TCZ therapy for caAMR or MVI + DSA-C4d- is associated with an improvement of eGFR trajectories, reduced DSA numbers and MFI and histological inflammation in glomeruli. These data suggest a potential benefit of TCZ in these settings.